"Fear and trembling" by Amélie Nothomb: Autobiography as a dialogue between imagined communities - Rámila Díaz, Noemi (Círculo de Lingüística Aplicada a la Comunicación, 2012)
The aim of this article is to explore the process undergone by the protagonist of Stupeur et Tremblement (Fear and trembling) by Amélie Nothomb. As this process is believed to be a dialogue between cultures, a Bakhtinian approach has been taken to illuminate its development towards a final understanding. In addition, the multiple sites of conflict and identity negotiation in the data are analyzed following Pavlenko’s main aspects of identity negotiation (2001b). One of the peculiarities about Amèlie Nothomb is that she considers Japanese and French as two ‘varieties’ of her mother tongue, although all her novels are written in French.